2017
DOI: 10.1007/s11571-017-9450-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between short and fast brain timescales

Abstract: Brain electric activity exhibits two important features: oscillations with different timescales, characterized by diverse functional and psychological outcomes, and a temporal power law distribution. In order to further investigate the relationships between low- and high- frequency spikes in the brain, we used a variant of the Borsuk-Ulam theorem which states that, when we assess the nervous activity as embedded in a sphere equipped with a fractal dimension, we achieve two antipodal points with similar feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…Temporal hierarchy in the cortex is organized from short to long temporal receptive windows (TRWs) (Hasson et al 2008), which is also thought to reflect a region's location along a unimodal to transmodal gradient, respectively (Margulies et al 2016, Huntenburg et al 2018. Longer timescale processing may reflect recurrent connections between higher-order association cortices (e.g., DMN) that enable the ability to integrate newly arriving information while also maintaining an internal working model of one's environment and cognitive state , Chaudhuri et al 2015, Déli et al 2017. Given the immaturity of the DMN during middle childhood (Fair et al 2009, Supekar et al 2010, de Bie et al 2012, Muetzel et al 2016, perhaps the development of long timescale processing reflects the refinement of these cortical gradients; however the current study cannot address these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporal hierarchy in the cortex is organized from short to long temporal receptive windows (TRWs) (Hasson et al 2008), which is also thought to reflect a region's location along a unimodal to transmodal gradient, respectively (Margulies et al 2016, Huntenburg et al 2018. Longer timescale processing may reflect recurrent connections between higher-order association cortices (e.g., DMN) that enable the ability to integrate newly arriving information while also maintaining an internal working model of one's environment and cognitive state , Chaudhuri et al 2015, Déli et al 2017. Given the immaturity of the DMN during middle childhood (Fair et al 2009, Supekar et al 2010, de Bie et al 2012, Muetzel et al 2016, perhaps the development of long timescale processing reflects the refinement of these cortical gradients; however the current study cannot address these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Further, theory of mind is a complex ability that involves the coordination of multiple skills (e.g., face recognition, emotion processing, predicting behavior) (Schaafsma et al 2015), many of which operate on diverse timescales. Thus, longer timescales may be needed to track, accumulate, and refine an accurate representation of mental states (Déli et al 2017), which is essential to one's ability to predict the social environment (Koster-Hale and Saxe 2013). While we found that long timescales were important for children's social-cognitive comprehension, the current study used a coarse temporal resolution (intact and scrambled).…”
Section: Discussionmentioning
confidence: 99%
“…(2) The neural energy can be combined with spiking pattern of membrane potentials to resolve the neural information (Wang et al, 2006 , 2008 , 2016 , 2017 ; Wang and Wang, 2014 ; Wang R. et al, 2014 ; Wang Z. et al, 2014 ; Kozma, 2016 ; Yan et al, 2016 ; Zheng et al, 2016 ). (3) Neural energy can describe the interaction of large-scale neurons referring to the interaction of multiple brain regions that cannot be achieved by any conventional coding theory (Wang et al, 2009 ; Vuksanović and Hövel, 2016 ; Zhang et al, 2016 ; Déli et al, 2017 ; Peters et al, 2017 ). (4) Currently, a simultaneous recording from multiple brain regions in traumatic brain injury experiments is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…However, the neuronal electric activities generated by the transmembrane flow of ions not only modulate the synaptic connection but also inevitably produce a time-varying electric field as well as a magnetic field, according to Maxwell’s theory of electromagnetic induction 3436 . This spontaneous magnetic field around neurons may be the foundation of brain transferring sensory stimulus via complex electromagnetic flows to the cortex 37 and has significant effects on the dynamical properties of neurons and neuronal networks 34,38–41 ; for example, it induces multiple firing modes of neurons 42,43 , promotes the double coherence resonance, inhibits the stochastic resonance 40 and modulates spatiotemporal patterns 44 . Meanwhile, magnetic field interactions between neurons support a potential spatial channel for neural information transmission 45,46 and can significantly modulate signal communications between neurons 45,47 , induce firing synchronization 48,49 , trigger complex mode transitions of electrical activities 5053 , and even offset the effect of a blocked potassium ion channel on the collective dynamics 54 .…”
Section: Introductionmentioning
confidence: 99%